The innovative culture of teachers between motivation, experience, and professional commitment - PIRAU, Lucia; BACIU, Sergiu (Acta et Commentationes, Sciences of Education, 2026)
Teachers’ innovative culture is a multidimensional construct that influences educators’ ability to identify innovative competencies, to maintain motivation in the face of change, and to disseminate innovative best practices. This article examines three hypotheses concerning the correlations between teaching experience, professional rank, motivation and commitment to the implementation of innovations, and involvement in the dissemination of innovative best practices. The literature review indicates that the development of an active innovative culture involves both individual and institutional factors, including professional experience, intrinsic and extrinsic motivation, and effective dissemination strategies.